ANALISA SENTIMEN PADA REVIEW OPERATOR SELULER 3 (TRIINDONESIA) TERHADAP MEDIA SOSIAL (TWITTER) MENGGUNAKAN METODE NAÏVE BAYES CLASSIFIER - Nur Masita , Desy; Zein Vitadiar , Tanhella; Lazulfa , Indana; Widoyoningrum , Sri (Inovate, 2024)
Cellular operators are service products that provide services to users, one of which is cellular operators 3. The use of services by cellular operators has negative and positive ratings, therefore researchers make observations on the use of cellular operators by using sentiment analysis to determine positive or negative values. In the sentiment analysis, the researcher used the naïve Bayes method to draw conclusions from the observed ratings in negative, positive, and neutral forms. Observing this, the researcher conducted an assessment on social networks, namely Twitter. Because on these social networks users can usually express evaluations of whatever they feel like using cellular operators 3. So the results obtained from sentiment assessments can be in the form of tweets such as signal disturbances, internet errors, and regarding good service as a consideration for improving the quality of cellular operators 3. Through this sentiment analysiscan help researchers to easily get a classification of positive, negative and neutral values.Keywords: Cellular Operators, Twitter, Naïve Bayes.